Ten Years of Positive Impact of a Conservation Education Program on Children's Knowledge and Behaviour Toward Crested Macaques (Macaca nigra) in the Greater Tangkoko Area, North Sulawesi, Indonesia - Mathilde Chanvin; François Lamarque; Nona Diko; Muhammad Agil; Jérôme Micheletta; Anja Widdig (International Journal of Primatology, 2023)
In areas where primates are threatened, environmental education interventions are a key way to increase the local population’s knowledge of their environment and encourage positive attitudes and habits to preserve the environment and wildlife on a local and global scale. This study assesses the impact of Tangkoko Conservation Education (TCE), the Macaca Nigra Project’s conservation education programme, running since 2011 in North Sulawesi for school children, teachers, and the local population. TCE’s goal is to help people increase their knowledge of their environment and develop more positive habits and behaviours towards their local environment, especially the Critically Endangered and endemic crested macaques ( Macaca nigra ). We measured the efficacy of TCE’s programme for pupils using questionnaires provided one month before and one month after a year-long conservation education programme at school. Pupils’ knowledge and behaviour scores increased significantly after their participation in the programme. Their habits score also increased but this increase was not statistically significant. Girls scored significantly higher than boys in terms of positive behaviour towards wildlife. Children participating in the programme more than once seemed to obtain higher scores in their second participation, although the sample size was too small for formal analysis. Despite some limitations, this study demonstrates the positive impact of our programme on young people living in an area where primates are threatened. We hope that this research will inspire similar programmes in Sulawesi and elsewhere by providing methods and activities to help prevent primate extinction.